2002
DOI: 10.1128/jvi.76.24.12414-12422.2002
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of Ex Vivo-Activated Human Immunodeficiency Virus Type 1-Specific Gamma-Interferon-Producing CD8+T Cells in Infected Children Correlate Positively with Plasma Viral Load

Abstract: HIV-specific CD8؉ -T-cell subset is dependent upon continuous antigenic stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 77 publications
6
23
2
Order By: Relevance
“…These observations alone provide strong evidence that MHC class I presentation of Gag epitopes will be essential for the effectiveness of HIV-1 vaccines and concur with the data found from macaque studies. In agreement with other studies (28,29), we have recently shown (30) that there is a positive correlation between total HIV-1-specific CD8 ϩ T cell responses and viral load, but a significant correlation between preferential targeting of Gag by CD8…”
Section: Depletion Of Cd8supporting
confidence: 80%
See 1 more Smart Citation
“…These observations alone provide strong evidence that MHC class I presentation of Gag epitopes will be essential for the effectiveness of HIV-1 vaccines and concur with the data found from macaque studies. In agreement with other studies (28,29), we have recently shown (30) that there is a positive correlation between total HIV-1-specific CD8 ϩ T cell responses and viral load, but a significant correlation between preferential targeting of Gag by CD8…”
Section: Depletion Of Cd8supporting
confidence: 80%
“…77 SLYNT VATL 86 (SL-9) and 76 RSLYNTVATLY 86 (RY-11), restricted by HLA-A*0201 and HLA-A*30, respectively (28,29). In our study, we also identified the RY-11 epitope (Fig.…”
Section: Optimal Epitope Recognition and Hla Restrictions In P17mentioning
confidence: 53%
“…ϩ T-cell responses and viremia in those on combination ART (25,26,29) and greater CTL responses were in children with persistent viremia after treatment (16,27,30). Our findings are similar to the CTL responses found in subjects with both detectable and undetectable viremia except for their finding of the significantly lower response noted in subjects with viral suppression and greater overall magnitude in CTL responses in both groups (16).…”
Section: Discussionsupporting
confidence: 79%
“…The findings in that study were different from ours as previously mentioned. Previous investigators have used recombinant vaccinia vectors expressing single specific viral proteins but not all HIV-1 proteins at once (15,17,(25)(26)(27)(28)30,31) or tetrameric complexes (17,29,30). Most authors have measured IFN-␥ by ELISpot assays, as we did, with the exception of those who used chromium release assays to measure CTL responses (15,17,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation